Invasive fungal infections in patients with multiple myeloma: a possible growing problem in hematology and infectious diseases - Toni Valkovic; Lucija Marcelic; Frane Valkovic (Therapeutic Advances in Infectious Disease, 2024)
Multiple myeloma is among the most common hematological malignancies and is characterized by a strong susceptibility to infections primarily bacterial and viral and, to a much lesser extent, fungal. There appears to be a slightly increasing frequency of invasive fungal infections. This is attributed to the use of different combinations of newer drugs and patients’ exposure to increasing therapeutic lines, and thus to risk factors for invasive fungal infections, especially severe and long-term neutropenia. Novel immunotherapy modalities including bispecific antibodies and chimeric antigen receptor T-cell therapy are being introduced for the treatment of relapsing-refractory forms of the disease. Consequently, in the near future, it can be expected that myeloma patients will exhibit a significantly increased frequency of invasive fungal infections. Therefore, we must carefully monitor all epidemiological trends related to invasive fungal infections in patients with multiple myeloma, both in clinical studies and in real life. This will help us learn to prevent fungal infections, as well as quickly recognize and treat them to reduce their impact on patients’ morbidity and mortality. In this review article, we describe in detail the epidemiological characteristics of invasive fungal infections in myeloma patients, the risk factors for these infections, and the treatment and prevention options.